2018
DOI: 10.3164/jcbn.17-97
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of inorganic phosphorus has a stronger influence on vascular-endothelium function than organic phosphorus

Abstract: Phosphorus management through dietetic therapy is vital for the prevention of cardiovascular disease in chronic kidney disease patients. There are two main sources of phosphorus in the diet, organic phosphorus from protein and inorganic phosphorus from food additives. The adverse effects of high phosphorus intake on vascular-endothelium function have been reported; however, the differences in the effects of organic phosphorus versus inorganic phosphorus are not clear. In this study, we examined an acute effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Kawamura et al. 14 compared 2 meals of equal phosphorus content but with different phosphorus sources (phosphorus supplement or natural phosphorus sources). They found a higher plasma phosphate after ingestion of phosphorus supplements compared to that after consumption of a meal with a high natural phosphorus content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawamura et al. 14 compared 2 meals of equal phosphorus content but with different phosphorus sources (phosphorus supplement or natural phosphorus sources). They found a higher plasma phosphate after ingestion of phosphorus supplements compared to that after consumption of a meal with a high natural phosphorus content.…”
Section: Discussionmentioning
confidence: 99%
“…However, the acute effects of meals with varying degrees of phosphorus-containing meals on the postprandial levels of plasma phosphate is sparsely described. A few studies have been conducted in healthy subjects 10 , 11 , 12 , 13 , 14 and in subjects with CKD stage 3 to 4, 15 but none have been conducted in subjects with ESKD. 16 This study aimed to investigate how a single meal with high phosphorus content acutely affects plasma phosphate compared to a single meal with low phosphorus content in patients with ESKD treated with peritoneal dialysis (PD).…”
mentioning
confidence: 99%
“…International Publisher of additives in processed foods has strong impacts on vascular endothelial functions [7][8][9].…”
Section: Ivyspringmentioning
confidence: 99%
“…However, studies in human have yielded conflicting evidence. Studies in young healthy men showed that brachial artery flow-mediated dilation (FMD), an indirect index of endothelial function, was reduced acutely after consumption meals containing inorganic Pi additives between 800-1200 mg [35][36][37], while FMD was unaffected by meals with 400 mg of inorganic Pi additives [36]. A longer term study showed reduction in brachial artery FMD after 2 weeks of high Pi (1,500 mg/day) administration in healthy middle-aged adults [32].…”
Section: Role Of Phosphotoxicity On Endothelial Cells and Vascular Smmentioning
confidence: 99%